J. Baltrušaitis’ Idea of Doubleworldness in Linguopoetic Interpretation - Чичинскaйте, Р. (Kalbotyra, 1990)
This article deals with the poetic symbol structure as the dynamics of poetic sense. This poetic sense can be expressed by a figurative restructuring of the lesome, taking into account its modality. The most significant way of symbolization in J. Baltrušaitith idiostyle is antithesis. The canonic idea of double-worldness is usually realized with its help.